Male circumcision for HIV prevention in high HIV prevalence settings: what can mathematical modelling contribute to informed decision making? - UNAIDS/WHO/SACEMA Expert Group on Modelling the Impact and Cost of Male Circumcision for HIV Prevention (PLoS Medicine)
Experts from UNAIDS, WHO, and the South African Centre for Epidemiological Modelling report their review of mathematical models estimating the impact of male circumcision on HIV incidence in high HIV prevalence settings.